Up-Regulation of ProBDNF/p75NTR Signaling in Spinal Cord Drives Inflammatory Pain in Male Rats - Li H; Liu T; Sun J; Zhao S; Wang X; Luo W; Luo R; Shen W; Luo C; Fu D (Dove Medical Press, 2023)
Hui Li,1,2,* Tao Liu,1,2,* Jingjing Sun,1,2 Shuai Zhao,1,2 Xin Wang,1,2 Wei Luo,1,2 Ruyi Luo,1,2 Weiyun Shen,1,2 Cong Luo,1,2 Di Fu3 1Department of Anesthesiology, the Second Xiangya Hospital, Central South University, Changsha, People's Republic of China; 2Hunan Province Center for Clinical Anesthesia and Anesthesiology, Research Institute of Central South University, Changsha, People's Republic of China; 3Department of Anesthesiology, the XiangYa Hospital, Central South University, ChangSha, People's Republic of China*These authors contributed equally to this workCorrespondence: Di Fu, Department of Anesthesiology, the XiangYa Hospital, Central South University, Xiangya Road No. 86, Changsha, Hunan Province, 410011, People's Republic of China, Tel/Fax +86 85295987, Email xyyyfudi@csu.edu.cnBackground: The spinal cord expresses brain-derived neurotrophic factor precursor (proBDNF) and its receptor pan neurotrophin receptor 75 (p75NTR). However, the role of spinal proBDNF signaling in the pathogenesis of inflammatory pain remains unknown.Methods: Rats were locally injected with complete Freund's adjuvant (CFA) to induce inflammatory pain. The proBDNF signal expression was detected by double-labeled immunofluorescence. ProBDNF protein, p75NTR extracellular domain (p75NTR-ECD), or monoclonal anti-proBDNF (McAb-proB) were administrated by intrathecal injection to investigate their effects on pain behavior. Paw withdrawal thermal latency (PWL) and paw withdrawal mechanical threshold (PWT) were performed to evaluate pain behavior. Immunoblotting, immunohistochemistry, and immunofluorescence were used to assess inflammation-induced biochemical changes.Results: CFA induced a rapid increase in proBDNF in the ipsilateral spinal cord, and immunofluorescence revealed that CFA-enhanced proBDNF was expressed in NeuN positive neurons and GFAP positive astrocytes. The administration of furin cleavage-resistant proBDNF via intrathecal injection (I.t.) significantly decreased the PWT and PWL, whereas McAb-proB by I.t. alleviated CFA-induced pain-like hypersensitivity in rats. Meanwhile, CFA administration triggered the activation of p75NTR and its downstream signaling extracellular signal-regulated kinase 1/2 (ERK1/2) and nuclear factor (NF)-kappaB p65 in the spinal cord. I.t. administration of p75NTR-ECD suppressed CFA-induced pain and neuroinflammation, including the expression of p-ERK1/2, p-p65, and the gene expression of tumor necrosis factor-α (TNF-α), and interleukin 6 (IL-6).Conclusion: Our study reveals that the activated proBDNF/p75NTRsignaling in the spinal cord contributes to the development of CFA-induced inflammatory pain. McAb-proB and p75NTR-ECD appear to be promising therapeutic agents for inflammatory pain.Keywords: brain-derived neurotrophic factor precursor, inflammatory pain, spinal cord, neuron, pan neurotrophin receptor 75